Isolation and function of a human endothelial cell C1q receptor - M. R. Daha; L. Dunn; R. van den Berg; Y. Muizert-de Lange; A. Gerritsen; L. A. van Es (Mediators of Inflammation)
It has been shown previously that cultured human venous and arterial endothelial cells (EC) bind C1q in a time- and dose-dependent manner. Cultured human endothelial cells express an average number of 5.2 × 105 binding sites/cell. In the present study the putative receptor for C1q (C1qR) was isolated from the membranes of 1–5 × 109 human umbilical cord EC by affinity chromatography on C1q–Sepharose. During isolation, C1qR was detected by its capacity to inhibit the lysis of EAC1q in C1q-deficient serum. The eluate from C1q–Sepharose was concentrated, dialysed and subjected to QAE-A50 chromatography and subsequently to gel filtration on HPLC–TSK 3000. C1qR filtered at an apparent molecular weight of 60 kDa. Purified C1qR exhibited an apparent molecular weight of 55–62 kDa in the unreduced state and a molecular weight of 64–68 kDa in reduced form. Two IgM monoclonal antibodies (mAb) D3 and D5 were raised following immunization of mice with purified receptor preparations. Both monoclonal antibodies increased the binding of 125I-C1q to endothelial cells but F(ab')2 anti-C1qR mAb inhibited the binding of a125I-C1q to EC in a dosedependent manner. The D3 mAb recognized a band of 54–60 kDa in Western blots of membranes of human EC and polymorphonuclear leukocytes. Previously, the authors showed that C1q induces the binding of IgM-containing immune complexes to EC. Therefore, it was hypothesized that during a primary immune response generation of IgM-IC may occur, resulting in binding and activation of C1, dissociation of activated C1 by C1 inhibitor and subsequent interaction of IgM-IC bearing C1q with EC–C1qR.